Sharia Company Tax Aggressiveness on the Jakarta Islamic Index (JII) during the COVID-19 Pandemic - Dewi Pudji Rahayu; Fernandes Simangunsong; Marja Sinurat; Meltarini; Mansyur (Agregat: Jurnal Ekonomi dan Bisnis, 2023)
Tax authorities need to look at the factors that drive tax aggressiveness. Moreover, some businesses designated as sharia companies, whose activities should comply with Islamic religious law, engage in tax aggressiveness that does not follow sharia. This study aimed to examine the effect of compensation and corporate social responsibility (CSR) on tax aggresiveness during the COVID-19 pandemic. The COVID-19 pandemic, 2020-2021. The analysis used hypothesis testing with statistical tools and a sample of 55 sharia companies listed on the Jakarta Islamic Index (JII). The compensation variable had no significant effect on tax aggressiveness, while only corporate environmental performance (CEP) was significant regarding the CSR variable. However, these two variables simultaneously have a relationship with tax aggressiveness. This research ran during the pandemic when conditions were not ceteris paribus. Thus, some theories might experience anomalies. The pandemic led to several anomalous theories. Moreover, the sample companies are sharia-based. CSR has three different theories: (1) There is influence, (2) There is no influence, and (3) Influence depends on natural activities. This study supports the third theory, whereby spontaneous activities influence corporate environmental performance (CEP), corporate governance performance (CGP), and corporate social performance (CSP).